Stretchable ECM Patch Enhances Stem Cell Delivery for Post‐MI Cardiovascular Repair. Issue 17 (15th July 2019) - Kim, In Gul; Hwang, Mintai P.; Park, Jin Sil; Kim, Su‐Hyun; Kim, Jung‐Hyun; Kang, Hyo Jin; Subbiah, Ramesh; Ko, Ung Hyun; Shin, Jennifer H.; Kim, Chong‐Hyun; Choi, Donghoon; Park, Kwideok
Abstract: Current cell‐based therapies administered after myocardial infarction (MI) show limited efficacy due to subpar cell retention in a dynamically beating heart. In particular, cardiac patches generally provide a cursory level of cell attachment due to the lack of an adequate microenvironment. From this perspective, decellularized cell‐derived ECM (CDM) is attractive in its recapitulation of a natural biophysical environment for cells. Unfortunately, its weak physical property renders it difficult to retain in its original form, limiting its full potential. Here, a novel strategy to peel CDM off from its underlying substrate is proposed. By physically stamping it onto a polyvinyl alcohol hydrogel, the resulting stretchable extracellular matrix (ECM) membrane preserves the natural microenvironment of CDM, thereby conferring a biological interface to a viscoelastic membrane. Its various mechanical and biological properties are characterized and its capacity to improve cardiomyocyte functionality is demonstrated. Finally, evidence of enhanced stem cell delivery using the stretchable ECM membrane is presented, which leads to improved cardiac remodeling in a rat MI model. A new class of material based on natural CDM is envisioned for the enhanced delivery of cells and growth factors that have a known affinity with ECM. Abstract : Here, an intriguing strategy is proposed to detach cell‐derived extracellular matrix (CDM) from its underlying substrate by physically stamping it onto a polyvinyl alcohol hydrogel which suggests potential as a cardiac patch. It also provides a dynamic environment in which cells directly interact with CDM under the cyclic tensional forces.